Palm biochar-based sulphated zirconium (Zr-AC-HSO3) catalyst for methyl ester production from palm fatty acid distillate - Rashid, Umer; Soltani, Soroush; Choong, Thomas Shean Yaw; Nehdi, Imededdine Arbi; Ahmad, Junaid; Ngamcharussrivichai, Chawalit (MDPI, 2019)
A palm waste kernel shell biomass was converted into bio-based sulphonated activated carbon and further used for preparation of a sulphated zirconium-doped activated catalyst (Zr-AC-HSO3) by wet impregnation method. The structural, physicochemical, morphological, textural, and thermal characteristics of the synthesized Zr-AC-HSO3 catalyst were characterized by X-ray diffraction (XRD), Brunauer–Emmett–Teller (BET) surface area analysis, temperature-programmed desorption of ammonia (TPD-NH3), Fourier transform infrared spectroscopy (FT-IR), and scanning electron microscopy (SEM). The catalytic activity of the 20 wt% Zr-AC-HSO3 catalyst was further evaluated for esterification of palm fatty acid distillate (PFAD). This study achieved a maximum fatty acid methyl ester (FAME) yield of 94.3% and free fatty acid (FFA) conversion of 96.1% via the esterification over 20 wt% Zr-AC-HSO3 using 3 wt% catalyst concentration, 15:1 methanol:PFAD molar ratio at 75 °C for 3 h. The experiments to test for reusability showed that the spent catalyst was stable for five successive reaction cycles, with a FFA conversion of 80% in the fifth cycle, without additional treatment. The critical fuel features of the synthesized PFAD methyl ester were determined and were within the range of EN14214 and ASTM D6751 standards.